Pravoslavná „Óda na radost“ - Stanislav Rubáš (Svět Literatury, 2022)
Drawing on the extensive research on the life and thought of the German poet Friedrich Schiller (1759–1805), most prominently by his biographers Gotthold Deile and Aleksandr Ivanovich Kirpichnikov, the paper outlines the genesis of Schiller’s “Ode to Joy,” a 1785 Masonic festive song, which has become an iconic poem of the European Enlightenment. Consequently, the author compares Schiller’s source text with its renowned 1823 translation by the Russian poet Fyodor Ivanovich Tyutchev (1803–1873). Schiller’s poem, filled with blatantly sacrilegious or, at least, unorthodox Masonic undertones, was transformed by Tyutchev into a Russian Orthodox choral, providing the translation studies scholar a unique opportunity to expound on one of the most typical imprints of Russian spirituality in the history of translation and interpretation.